2011
DOI: 10.1159/000323004
|View full text |Cite
|
Sign up to set email alerts
|

Nail Psoriasis Successfully Treated with Intralesional Methotrexate: Case Report

Abstract: Psoriasis is a common, chronic disease which affects nearly 3% of the population. The lifetime incidence of nail involvement increases up to 80–90% for psoriatic patients. Nail psoriasis is considered a significant social problem. Many topical agents have been used for psoriatic nails with various side effects and some benefits; management is currently inconclusive. Methotrexate (MTX) is a folic acid analog, which irreversibly binds to dehydrofolate reductase and blocks deoxyribonucleic acid synthesis. It is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 28 publications
2
35
0
1
Order By: Relevance
“…Another medication that has been used intralesionally for the treatment of nail psoriasis is methotrexate. It was used at a dose of 2.5 mg in one patient with severe psoriatic nail disease with good results (25). A weekly injection during 6 weeks improved significantly the subungual hyperkeratosis and pitting, and the result was maintained after 2 years.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another medication that has been used intralesionally for the treatment of nail psoriasis is methotrexate. It was used at a dose of 2.5 mg in one patient with severe psoriatic nail disease with good results (25). A weekly injection during 6 weeks improved significantly the subungual hyperkeratosis and pitting, and the result was maintained after 2 years.…”
Section: Treatmentsmentioning
confidence: 99%
“…It was used at a dose of 2.5 mg in one patient with severe psoriatic nail disease with good results (25). It was used at a dose of 2.5 mg in one patient with severe psoriatic nail disease with good results (25).…”
Section: Treatmentsmentioning
confidence: 99%
“…MTX 2.5 mg was injected into each side of the proximal nail fold once weekly for 6 weeks. [75] Pain was tolerable. During the 4-month follow-up, the psoriatic nail alterations improved and no clinical or laboratory side effects were noted.…”
Section: Treatment Of Nail Psoriasismentioning
confidence: 99%
“…Saricaoglu et al [37] reported a case of severe psoriatic nail disease successfully treated with intralesional methotrexate at a dose of 2.5 mg of weekly injections for 6 weeks. The significant improvement in subungual hyperkeratosis and pitting was maintained after 2 years of treatment.…”
Section: Intralesional Therapymentioning
confidence: 99%